Copy number alteration of neuropeptides and receptors in multiple cancers - Min Zhao (Nature Portfolio, 2017)
Abstract Neuropeptides are peptide hormones used as chemical signals by the neuroendocrine system to communicate between cells. Recently, neuropeptides have been recognized for their ability to act as potent cellular growth factors on many cell types, including cancer cells. However, the molecular mechanism for how this occurs is unknown. To clarify the relationship between neuropeptides and cancer, we manually curated a total of 127 human neuropeptide genes by integrating information from the literature, homologous sequences, and database searches. Using human ligand-receptor interaction data, we first identified an interactome of 226 interaction pairs between 93 neuropeptides and 133 G-protein coupled receptors. We further identified four neuropeptide-receptor functional modules with ten or more genes, all of which were highly mutated in multiple cancers. We have identified a number of neuropeptide signaling systems with both oncogenic and tumour-suppressing roles for cancer progression, such as the insulin-like growth factors. By focusing on the neuroendocrine prostate cancer mutational data, we found prevalent amplification of neuropeptide and receptors in about 72% of samples. In summary, we report the first observation of abundant copy number variations on neuropeptides and receptors, which will be valuable for the design of peptide-based cancer prognosis, diagnosis and treatment.